Adsorption Characteristics and Charge Transfer Kinetics of Fluoride in Water by Different Adsorbents - Tang, Jiaxi; Xiang, Biao; Li, Yu; Tan, Ting; Zhu, Yongle (Frontiers in Chemistry, 2022)
Water containing high concentrations of fluoride is widely distributed and seriously harmful, largely because long-term exposure to fluoride exceeding the recommended level will lead to fluorosis of teeth and bones. Therefore, it is imperative to develop cost-effective and environmentally friendly adsorbents to remove fluoride from polluted water sources. In this study, diatomite (DA), calcium bentonite (CB), bamboo charcoal (BC), and rice husk biochar (RHB) were tested as adsorbents to adsorb fluoride (F‐) from water, and this process was characterized by scanning electron microscopy (FEI-SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FT-IR). The effects of pH, dosage, and the initial mass concentration of each treatment solution upon adsorption of F‐ were determined. Kinetic and thermodynamic models were applied to reveal the mechanism of defluoridation, and an orthogonal experiment was designed to obtain the optimal combination of conditions. The results show that the surfaces of CB, BC, and RHB have an irregular pore structure and rough surface, whereas DA has a rich pore structure, clear pores, large specific surface area, and high silica content. With regard to the adsorption process for F‐, DA has an adsorption complex electron interaction; that of CB, BC, and RHB occur mainly via ion exchange with positive and negative charges; and CB on F‐ relies on chemical electron bonding adsorption. The maximum adsorption capacity of DA can reach 32.20 mg/g. When the mass concentration of fluoride is 100 mg/L, the pH value is 6.0 and the dosage is 4.0 g/L; the adsorption rate of F‐ by DA can reach 91.8%. Therefore, we conclude that DA soil could be used as an efficient, inexpensive, and environmentally friendly adsorbent for fluoride removal, perhaps providing an empirical basis for improving the treatment of fluorine-containing water in the future.